Abordagem histórica do curso de Pedagogia e o trabalho do pedagogo em espaço não escolar! - Fernandes, Andrielly Borges Azevedo (Universidade Federal do Tocantins, 2022)
The present work aimed to present a study on the history of the formation of the pedagogy course in Brazil and that of the UFT/Campus de Miracema, and then to observe the need and importance of the pedagogue's work in a non-school environment, especially the case of a hospital institution. We opted for a qualitative methodological approach and bibliographic study, due to the difficulties imposed by the pandemic. Education takes place in all spaces where there are human practices. The pedagogy course has a long history of contributions in teacher training for teaching work in school institutions, but this does not mean denying the debate on the existence of education and pedagogical practices in other spaces. The work developed by the pedagogue in a hospital space must be different from what happens in the school, because the situations that the students are in are very different, so the methodologies and activities must be elaborated for each situation. It is considered important that there is a deepening of this debate in the formation of the pedagogue and, as far as possible, its articulation in the course curriculum.